2022
DOI: 10.1021/acsanm.2c00416
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Growth of Reactive Pyrochlore Nanostructures on Zirconia-Supported Ceria: Implications for Improved Catalytic Behavior

Abstract: The use of a catalyst support for the design of nanoscale heterogeneous catalysts based on cerium oxide offers vast possibilities for future catalyst development, particularly with regard to an increased focus on the use of renewable biogas and an emerging hydrogen economy. In this study, zirconia-supported ceria catalysts were synthesized, activated by using different thermochemical treatments, and characterized by way of temperature-programmed reduction (TPR), oxygen storage capacity, X-ray diffraction, elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 56 publications
(84 reference statements)
0
2
0
Order By: Relevance
“…In conclusion, the improvement of the reducibility of the sample at low temperature can be attributed to the presence of the Ce/Zr pyrochlore monolayer in the case of SO-SRMO sample, in good agreement with previously reported results. 18 , 20 , 21 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, the improvement of the reducibility of the sample at low temperature can be attributed to the presence of the Ce/Zr pyrochlore monolayer in the case of SO-SRMO sample, in good agreement with previously reported results. 18 , 20 , 21 …”
Section: Resultsmentioning
confidence: 99%
“…Zirconia- and yttria-stabilized zirconia (YSZ)-supported ceria systems have been recently investigated. 18 , 19 , 20 Temperature-programmed reduction treatments have revealed that the reducibility of YSZ-supported ceria can be largely enhanced after a so-called strong reduction mild oxidation (SRMO) treatment, which consists in a reduction at 900°C in a flux of H 2 (5% in Ar) for several hours followed by an oxidation at 500°C in O 2 (5% in He). The redox behavior of this SRMO-treated YSZ-supported catalyst is also superior to that of the bulk Ce/Zr mixed oxide of the same composition submitted to the same treatment.…”
Section: Introductionmentioning
confidence: 99%